Вплив дефектів дивакансія-кисень на рекомбінаційні властивості n-Si після опромінення та наступного відпалу - Kras’ko, M. M.; Kolosiuk, A. G.; Voitovych, V. V.; Povarchuk, V. Yu.; Roguts’kyi, I. S. (Publishing house "Academperiodika", 2018)
The variation of recombination properties in n-Si grown by the Czochralski method, doped to the free electron concentration n0 ∼ 10^14 ÷10^16 cm^−3, irradiated with 60Co y-quanta or 1-MeV electrons, and isochronously annealed for 20 min in the temperature interval 180–380∘C, in which divacancy-oxygen (V2O) complexes are formed and annealed, has been studied in detail. The nonequilibrium charge carrier lifetime т is found to significantly decrease after the annealing in a temperature interval from 180 to 280∘C, with the effect being stronger for low-resistive n-Si. It is shown that a change in т after the annealing at 180–380∘C is caused by divacancy defects, most probably V2O. By analyzing the experimental data with the help of the Shockley–Read–Hall statistics, it is found that the formation of V2O defects is characterized by an activation energy of 1.25±0.05 eV and a frequency factor of (1±0.5)×10^9 s^−1, and their annealing by an activation energy of 1.54±0.09 eV and a frequency factor of (2.1±1.4)×10^10 s^−1. The values of the hole capture cross-sections by singly and doubly charged acceptor states of V2O are obtained as: (5±2)×10^−13 and (8±4)×10^−12 cm^2, respectively.